Audiovisual aids and listening comprehension among tenth-grade students at a public institution in Loja. School year 2022-2023. - Jumbo Pardo, Luciana Nayely (2023)
Listening skills play a crucial role in English language learning and are essential for effective communication. In this sense, it is necessary to apply innovative resources that motivate students and help them to develop their listening skills. Therefore, the general objective of this study was to determine the effect of using audiovisual aids on listening comprehension skills among tenth-grade students at a public institution in Loja, during the 2022-2023 school year. Two specific objectives guided this research: to find out the effectiveness of audiovisual aids in listening comprehension skills and to describe the students' perceptions towards the use of audiovisual aids in listening comprehension skills. This study used a design of an action research model, with a mixed method among 38 participants to collect quantitative data, that was processed using descriptive statistics and qualitative data examined by thematic analysis. For this purpose, the following instruments were used: a test administered before and after the intervention, a questionnaire and field notes. The pretest and posttest results showed a noticeable improvement reflected in the participants' listening comprehension performance in terms of listening for gist, listening for details, and making inferences. Similarly, the questionnaire results revealed students' positive perceptions regarding the use of audiovisual aids to improve their listening skills. The conclusions of this study emphasized that the application of audiovisual aids in teaching English as a foreign language could be effective in developing learners' listening comprehension skills and that these aids also supported participants' motivation, improved the classroom environment, and encourage learners' active participation. Key words: EFL teaching, interactive videos, linear videos, listening sub-skills, multimedia, teaching materials.